Google Translate as a Supplementary Tool for Learning Malay: A Case Study at Universiti Sains Malaysia - Bahri, Hossein; Tengku Mahadi, Tengku Sepora (Australian International Academic Centre (AIAC), 2016)
The present paper examines the use of Google Translate as a supplementary tool for helping international students at Universiti Sains Malaysia (USM) to learn and develop their knowledge and skills in learning Bahasa Malaysia (Malay Language). The participants of the study were 16 international students at the School of Languages, Literacies, and Translation, USM who had registered for the LKM 100 Bahasa Malaysia (I) course. Based on the literature review, analysis of the collected data, and an assessment of the course content and activities inside and outside the language classroom, the findings suggest that most international students at USM recognize Google Translate as an effective supplementary tool for learning vocabulary, writing, and reading in Bahasa Malaysia. In fact, some students reported that they could optimally benefit from their self-learning if they were assisted to use Google Translate effectively. Moreover, using Google Translate for doing classroom tasks and activities can encourage students to study independently, and to shape their own strategies for solving language learning problems.